Evidence-based interventions to reduce maternal malnutrition in low and middle-income countries: a systematic review - Shenoy, Shivani; Sharma, Priyanka; Rao, Aishwarya; Aparna, Nusrat; Adenikinju, Deborah; Iloegbu, Chukwuemeka; Pateña, John; Vieira, Dorice; Gyamfi, Joyce; Peprah, Emmanuel (Frontiers in Health Services, 2023)
Introduction Despite remarkable strides in global efforts to reduce maternal mortality, low-and middle-income countries (LMICs) continue to grapple with a disproportionate burden of maternal mortality, with malnutrition emerging as a significant contributing factor to this enduring challenge. Shockingly, malnourished women face a mortality risk that is twice as high as their well-nourished counterparts, and a staggering 95% of maternal deaths in 2020 occurred within LMICs. The critical importance of addressing maternal malnutrition in resource-constrained settings cannot be overstated, as compelling research studies have demonstrated that such efforts could potentially save thousands of lives. However, the landscape is marred by a scarcity of evidence-based interventions (EBIs) specifically tailored for pregnant individuals aimed at combatting maternal malnutrition and reducing mortality rates. It is against this backdrop that our study endeavors to dissect the feasibility, adoption, sustainability, and cost-effectiveness of EBIs designed to combat maternal malnutrition. Methods Our comprehensive search encompassed eight prominent databases covering the period from 2003 to 2022 in LMICs. We began our study with a comprehensive search across multiple databases, yielding a total of 149 studies. From this initial pool, we eliminated duplicate entries and the remaining studies underwent a thorough screening process resulting in the identification of 63 full-text articles that aligned with our predefined inclusion criteria. Results The meticulous full-text review left us with a core selection of six articles that shed light on interventions primarily centered around supplementation. They underscored a critical issue -the limited understanding of effective implementation in these countries, primarily attributed to inadequate monitoring and evaluation of interventions and insufficient training of healthcare professionals. Moreover, our findings emphasize the pivotal role of contextual factors, such as cultural nuances, public trust in healthcare, the prevalence of misinformation, and concerns regarding potential adverse effects of interventions, which profoundly influence the successful implementation of these programs. Discussion While the EBIs have shown promise in reducing maternal malnutrition, their true potential for feasibility, adoption, cost-effectiveness, and sustainability hinges on their integration into comprehensive programs addressing broader issues like food insecurity and the prevention of both communicable and non-communicable diseases.